The occurrence of Sumatran tiger (Panthera tigris sumatrae) in an industrial plantation forest area, North Sumatra, Indonesia - Pindi Patana; Meta Winda Saputri; King Marpatasino (Indonesian Journal of Applied Environmental Studies, 2021)
Sumatran tiger lives in the remaining forests on the Sumatra island, both in conservation and production areas. There are not many tiger monitoring activities conducted in production forest. Using camera traps this occupancy survey of Sumatran tiger (Panthera tigris sumatrae) carried out in a plantation forest area of PT. Toba Pulp Lestari (PT. TPL)  to obtain information and monitor tiger presence in the area.  However, there were no Sumatran tigers captured by the camera traps during the occupancy activities. The existence of Sumatran tiger was proven by the finding of footprints and scrapes. Other species were photographed by the camera traps, such as marbled cat ((Pardofelis marmorata), pig-tailed monkey (Macaca nemestrina), treeshrew (Tupaia sp.), Asian palm civet (Paradoxurus hermaphroditus), lizards (Eutropis sp.), Hoogerwerfs pheasant (Lophura hoogerwerfi), wood mouse (Apodemus sylvaticus) as well as birds. It is assumed that the Sumatran tiger didnt cross the location of research during the camera installation period. However, there are several other reasons why Sumatran tigers werent captured by camera traps, such as the camera traps observation time was too short and didnt cover a larger area, so it lessens the opportunity of encounter with Sumatran tiger.Harimau Sumatera hidup di hutan yang masih tersisa di pulau Sumatera, baik di kawasan hutan konservasi maupun hutan produksi. Kegiatan pemantauan harimau di hutan produksi belum banyak dilakukan. Dengan menggunakan camera trap, survei okupansi harimau sumatera (Panthera tigris sumatrae) ini dilakukan di areal  konsesi hutan tanaman industri PT. Toba Pulp Lestari (PT. TPL) untuk mendapatkan informasi dan memantau keberadaan harimau di kawasan tersebut. Namun, tidak ada harimau sumatera yang terfoto oleh kamera trap selama kegiatan survei okupansi. Keberadaan harimau sumatera dibuktikan dengan ditemukannya jejak tapak dan cakaran. Selain itu, terdapat ppesies lain yang terfoto oleh kamera trap, seperti kucing batu ((Pardofelis marmorata), beruk (Macaca nemestrina), tupai tanah (Tupaia sp.), musang pandan (Paradoxurus hermaphroditus), kadal (Eutropis sp.), sempidan aceh (Lophura hoogerwerfi), tikus hutan (Apodemus sylvaticus) serta burung. Diasumsikan bahwa harimau sumatera tidak melintasi lokasi penelitian selama masa pemasangan kamera. Namun, terdapat beberapa alasan lain mengapa harimau sumatera tidak terfoto kamera trap, seperti waktu pengamatan kamera trap yang terlalu singkat dan tidak mencakup area yang lebih luas, sehingga memperkecil peluang perjumpaan dengan harimau sumatera.